Genetic characterization and inventory of the Bísaro pig through visible effect genes. Their utilization in the genotypic comparison between populations and in the establishing of a nucleus for in vivo genetic conservation - Santos e Silva J.; Bernardo A.; Pires da Costa J. (Tradition and innovation in Mediterranean pig production, 2000)
Observation in certain traditional pig farms of interior northern Portugal made it possible to identify animals which had visible variants (colour, shape and position of ears, head, size, dorsal line) that characterized the ancient Bísaro pig. Due to the importance of these observations in the field of genetic resource, they conducted the development of actions in the conservation, characterization and evaluation of that type of pig and had the objective of determining production and processing potentials. This study deals with the first phase of that project which includes the identification and characterization of the Bísaro pig: a quantitative and genetic inventory was carried out on the herd (Bísaro); a first selection of animals was made (based on visible traits). The aim of these measures was to create two in vivo genetic conservation nuclei (in Minho and Trás-os-Montes) where animals could be studied.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)